Oceanology - Nigmatulin, Robert I.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
Oceanology, founded in 1961, is the leading journal in all areas of the marine sciences. It publishes original papers in all fields of theoretical and experimental research in physical, chemical, biological, geological, and technical oceanology and reviews and information about cruises, conferences, symposia and other events of interest to the oceanographic community.
Keywords: Oceanography; Oceanography